2012
DOI: 10.1111/j.1526-4637.2012.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Water Physical Therapy on Pain, Pressure Pain Sensitivity, and Myofascial Trigger Points in Breast Cancer Survivors: A Randomized, Controlled Clinical Trial

Abstract: An 8-week water therapy program was effective for improving neck and shoulder/axillary pain, and reducing the presence of TrPs in breast cancer survivors as compared with usual care; however, no significant changes in widespread pressure pain hyperalgesia were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 40 publications
1
112
0
Order By: Relevance
“…In our study, the women continued weekly year after year, on their own initiative. This is positive since physical activity, for example, water-exercising, has well-known benefits in terms of general health benefits (Bränström et al, 2015;Chen et al, 2011;Lee et al, 2012;Wen et al, 2011) and arm specific benefits (Cantarero-Villanueva et al, 2012, 2013Fernández-Lao et al, 2013;Johansson et al, 2013;Linduist et al, 2015). Group-based water-exercising consume small economic resources, as compared to multimodal exercise programs for breast cancer survivors (Haines et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, the women continued weekly year after year, on their own initiative. This is positive since physical activity, for example, water-exercising, has well-known benefits in terms of general health benefits (Bränström et al, 2015;Chen et al, 2011;Lee et al, 2012;Wen et al, 2011) and arm specific benefits (Cantarero-Villanueva et al, 2012, 2013Fernández-Lao et al, 2013;Johansson et al, 2013;Linduist et al, 2015). Group-based water-exercising consume small economic resources, as compared to multimodal exercise programs for breast cancer survivors (Haines et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, we found that more female cancer survivors decreased their secondary lymphoedema volume after water exercise compared to land exercise (Linduist et al, 2015;n = 88). Water exercise reduced neck and arm pain n = 66), pain sensitivity (Cantarero-Villanueva et al, 2012;n = 44) and range of movement in the shoulder (Johansson et al, 2013;n = 25), as compared to no water exercise. Water reduced a variety of breast cancer related symptoms more than land-based exercise n = 98).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations